Evolution of high-temperature hardness of multimodal γ′ nickel-based superalloy - Yang Zhang; Yueming Fan; Kaili Feng; Chaoze Lu; Yihan Wang; Tianmin Shao (Journal of Materials Research and Technology, 2024)
Hardness reflects the comprehensive mechanical properties of materials, and its evolution during a wide temperature range reflects high-temperature performance. This study investigates the evolution of the high-temperature hardness of a nickel-based superalloy Ni16Cr13Co4Mo. Various thermal cycles featuring distinct peak heating temperatures were utilized to examine the variation of Vickers hardness with temperature. The effect of precipitated phases (specifically the γ′ phase) in the superalloy on high-temperature hardness and the deformation mechanism of the alloy was analyzed. The results show that the high-temperature hardness of the nickel-based superalloy decreases as temperature increases. However, the hardness after thermal cycles demonstrates an increase which is determined by the peak heating temperature. The increased hardness following thermal cycles is attributed to the reduction in size and the increase in the volume fraction of secondary γ′. Detailed TEM observation revealed that as the peak temperature increases, the deformation mechanism transforms from dislocation pile-ups in the γ matrix, dislocation and stacking fault shearing, microtwining in γ and γ′ phases to stacking fault shearing and piled-up dislocations in γ phase. As the result, hardness decreases as temperature increases.